Popular religion and ritual in prehistoric and ancient Greece and the eastern Mediterranean - Kaneloppulos, Chrysanthos; Kaneloppulos, Chrysanthos; Baburanakēs, Giōrgos; Baburanakēs, Giōrgos; Kopanias, K.; Kopanias, K. (Archaeopress archaeology, 2018)
This volume features a group of select peer-reviewed papers by an international group of authors, both younger and senior academics and researchers, on the frequently neglected popular cult and other ritual practices in prehistoric and ancient Greece and the eastern Mediterranean